Effect of genotype, irrigation and fertility on yield, nitrogen- recovery and its use efficiency in spring sunflower (Helianthus annuus) - TEJ SINGH; HARBIR SINGH; BALDEV RAJ (Indian Journal of Agronomy, 2001)
A 2-year field study was conducted with spring sunflower (Helianthus annuus L.) at Hisar, comprising 2 genotypes, 3 levels of irrigation and 5 levels of nitrogen + phosphorus. Sunflower hybrid MSFH 8 gave higher seed yield, N uptake, apparent N recovery as well as N-use efficiency. Scheduling irrigation at 0.6 ID :CPE ratio was better than other irrigation schedules for seed yield and N uptake at harvest. With each increment of N + P,O, level from 0 + 0 to 120 + 60 kglha, there was a significant increase in the seed yield as well as N uptake. Apparent recovery of applied N and N- use efficiency were higher when irrigation was scheduled at 0.6 ID :CPE ratio. Appli- cation of 30 + 15and 60 + 30 kg N + P,O,/ha recorded higher apparent N recovery and N-use efficiency.